One-Pot Multi Component Synthesis of 4-Arylaminoquinazolines in the Presence of Sodium 30-Tungstopentaphosphate - F. Bamoharram, Fatemeh; M. Heravi, Majid; Roshani, Mina; Monabati, Mahsa (Asian Journal of Chemistry, 2010)
A new multi-component synthesis of 4-arylaminoquinazolines from the reaction of 2-aminobenzamide, orthoesters and substituted anilines in presence of catalytic amounts of sodium 30-tungstopentaphosphate, so-called Preyssler heteropolyacid, is reported. The effects of solvent, amount of catalyst and aniline and reaction time were studied. Optimum conditions for synthesis of 4-arylaminoquinazolines have been obtained.